A discussion on qualitative research in physical activity - Munroe-Chandler , K. J. (Athletic Insight - The Online Journal of Sport Psychology, 2005)
Qualitative research in sport psychology has been increasingly on the rise, thereby allowing a greater understanding of the participant`s experiences (see Dale, 1996). Exercise psychologists (e.g., Gauvin, 1990; Golberg, 1992; Whaley & Ebbeck, 1997) have also employed qualitative methodologies in their investigations, although to a much lesser extent. Consequently, there remains a need for additional studies, particularly in exercise psychology, as well as a review article on the use and future direction of qualitative research in the physical activity field. The purpose of this article is to provide an overview of the various ways in which qualitative methodologies can and has contributed to the knowledge and understanding of physical activity research. The discussion is organized into four sections highlighting, (1) the competing paradigms, (2) qualitative research in sport psychology, (3) qualitative research in exercise psychology, and (4) the future of qualitative research in physical activity.